Heat Transfer Enhancement Of Lithium-Ion Battery Using Nanofluids - Asrab Ali, Muhammad Imran Salim (Universiti Sains Malaysia, 2018)
Electric Vehicle (EV) and Hybrid Electric Vehicles (HEV) are seen as the future of motor vehicles. HEVs depend little on conventional fuel and EVs do not depend on conventional fuel. This lead to future vehicle to become more eco-friendly with its low gas emission. The engine of these vehicles is run mainly on electrical supply. A prominent resource for these vehicles is Lithium-ion battery. The performance of Lithium-ion battery is essential for the car to sustain a long-term performance. One of the key factors in ensuring Lithium-ion battery performs to its best is by ensuring the battery is run on its optimal temperature. Battery performance changes dramatically with temperature. Maintaining the temperature of battery is done by cooling. Coolers role in performance of cars has been much bigger for EVs and HEVs. This research focuses on thermal management of battery by thermal enhancement using nanofluids as coolant. Analysis is done experimentally and through simulation to study the best composition of nanoparticles required in nanofluid to enhance heat transfer that leads to maintaining temperature of battery.